Engaging and working with African American fathers : strategies and lessons - Rollins, Latrice S (New York City : Routledge Books, 2020)
"Engaging and Working with African American Fathers: Strategies and Lessons challenges traditional and historic practices and policies that have systematically excluded fathers and contributed to social and health disparities among this population. With chapters led by African American women - drawing on years of research, interviews and practical experience with this demographic - each section explores current evidence on engagement approaches; descriptions of agencies/programs addressing specific issues fathers face, and case studies documenting typical clients and approaches to addressing their diverse needs. Offering an expansive overview of issues affecting African American fathers, the book explores such important topics as public, child and mental health; education; parenting; employment and public initiatives amongst others. Engaging and Working with African American Fathers is a key resource for social work, public health, education students, researchers, practitioners, policymakers, and members of communities who are challenged by meeting the diverse needs of African American fathers"--
OCLC-licensed vendor bibliographic record.
Keywords: African American fathers; SOCIAL SCIENCE / Sociology / General